ANALISIS TARIF PELAYANAN POLI PENYAKIT DALAM DI RUMAH SAKIT UMUM DAERAH DALAM ERA JAMINAN KESEHATAN NASIONAL - Sri Wusono; Julita Hendrartini; Dwi Handono Sulistyo (Journal of Health Service Management, 2020)
Background: The Hospital as an advanced health facility has an essential role in implementing the National Health Insurance (JKN).Reimbursement mechanism of health services using INA-CBGs package tariff, which the objectives for controlling healthcare costsand improving service standards. However, this has not been implemented well. Therefore INA-CBGs has a disadvantage potentialto Hospital.Objective: To determine the difference between Hospital tariff and INA-CBGs for JKN patients.Methods: This study was descriptive with a qualitative approach and case study design. Review documents and in-depth interviewswith Hospital structural and functional management were used for data collection. Data analyzed used descriptive analysis for secondarydata and qualitative analysis to explore hospital policies and strategies to the tariff difference to deepen this study result. Theresearch was conducted from April to June 2018.Results: Healthcare cost of JKN patients in Internal Disease Poly has negative difference during January–June 2017 with an averageof 20,3%. The main factor causing the difference was pharmaceutical 63%. This tariff difference occurred due to several factorssuch as related with the most morbidity diseases: 61,7% chronic diseases, policies implemented for capacity building of human resourcesin JKN patient services, improvement of a referral program for stable patients, cross-subsidizing of other income and government,specific strategies in JKN services that listed in the strategic plan. Furthermore, for service output was planned to reach hospitalaccreditation and conduct excellent heart disease service.Conclusion: Healthcare cost in Internal Disease Poly had deficit due to hefty deviation tariff between hospital tariff and INA-CBGs.However, potential losses could be anticipated with policies and strategies that support cost control and improve service standards.